Schaum's Outline of Theory and Problems of Statistics and Econometrics - Salvatore, Dominick (New York : McGraw-Hill, 1982)
This book presents a clear and concise introduction to statistics and econometrics. Each chapter begins with a statement of theory, principles or background information, fully illustrated with examples. This is followed by numerous theoretical and practical problems with detailed, step-by-step solutions. While primarily intended as a supplement to all current standard textbooks of statistics and/or econometrics, the book can also be used as an independent text as well as to supplement class lectures.
Cover title: Theory and problems of statistics and econometrics.
Spine title: Statistics and econometrics.
Includes bibliographical references and index.
ne 4/04/2018
Loan
Keywords: Social sciences; Statistics; Econometrics